The U‐shaped association between body mass index and gastric cancer risk in the Helicobacter pylori Biomarker Cohort Consortium: A nested case–control study from eight East Asian cohort studies. Issue 3 (12th December 2019) - Jang, Jieun; Wang, Tianyi; Cai, Hui; Ye, Fei; Murphy, Gwen; Shimazu, Taichi; Taylor, Philip R; Qiao, You‐Lin; Yoo, Keun‐Young; Jee, Sun Ha; Kim, Jeongseon; Chen, Sheau‐Chiann; et al.
Abstract : The association between body mass index (BMI) and noncardia gastric cancer (NCGC) risk remains controversial. The purpose of our study was to examine the association of BMI with NCGC risk with consideration of Helicobacter pylori (HP) biomarkers. This international nested case–control study, composed of 1, 591 incident NCGC cases and 1, 953 matched controls, was established from eight cohorts in China, Japan and Korea, where the majority of NCGCs are diagnosed worldwide. HP antibody biomarkers were measured in blood collected at cohort enrollment by multiplex serology. The NCGC risk according to baseline BMI was estimated using logistic regression to produce odds ratios (ORs) and 95% confidence intervals (CIs). We found a U‐shaped association between BMI category and NCGC risk. Compared to those with reference BMI (22.6–25.0 kg/m 2 ), those with lower and higher BMI had an increased NCGC risk (BMI <18.5 kg/m 2, OR = 1.56, 95% CI = 1.04–2.34; BMI >27.5 kg/m 2, OR = 1.48, 95% CI = 1.15–1.91; adjusted for age, sex and smoking). The U‐shaped association was persistent among subjects with HP infection and high‐risk biomarkers (HP+ CagA+: BMI <18.5 kg/m 2, OR = 1.60, 95% CI = 1.00–2.55; BMI >27.5 kg/m 2, OR = 1.59, 95% CI = 1.21–2.11; and Omp+ HP0305+: BMI <18.5 kg/m 2, OR = 1.88, 95% CI = 1.04–3.42; BMI >27.5 kg/m 2, OR = 1.70, 95% CI = 1.20–2.42, respectively). Our study provides evidence of significantly increased NCGC risk among individuals with low or high BMI, including in subjects with high‐risk HP biomarkers (HP+ CagA+, Omp+ HP0305+) in the high‐risk area of East Asia. Abstract : What's new? Gastric‐cancer (GC) mortality in East Asian countries accounts for 58% of GC deaths worldwide. Does body mass index (BMI) affect GC risk in these populations? In this prospective study, the authors found a U‐shaped association between BMI and non‐cardia GC risk. This association also held true for subjects with high‐risk biomarkers for Helicobacter pylori infection. These results indicate that maintaining normal body weight is important for reducing gastric‐cancer risk in East Asia, which may help guide public health strategies.